Analysis of Potential RDF Resources from MSW Landfills in Major Cities of Indonesia - Andre Susilo; Djoko M. Hartono; Muhammad Angga Kusuma; Dwica Wulandari (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
Many Indonesian landfills include the waste that has the potential to be used as an alternative fuel in the cement industry. It is converted into RDF to enable cement manufacturers to use waste. The research was conducted to know the Municipal Solid Waste (MSW) potential of 3 landfills (Bantargebang, Sumur Batu, and Cipayung) as a renewable fuel. Before processing, MSW is characterised because there are quality standards that the waste must meet before being used as fuel. That is a quantitative study combining a literature review and laboratory test methods. The parameters that have been measured from the three sample sites were water content, ash content, volatile level, and calorific value. The results showed that the total energy value acquired from Refuse Derived Fuel (RDF) resources of Bantargebang, Sumur Batu, and Cipayung landfills was 2742.14, 2741.24, and 2671.32 kcal/kg, respectively. In addition, based on the water content at the three sample locations, only rubber samples qualified for RDF processing. In contrast, rubber was the sole component that did not match the processing conditions to become RDF based on ash content. Furthermore, the volatile level of the three research sites meets the RDF standard.